New records of Myxomycetes (Amoebozoa) from the tropical Andes - Treviño-Zevallos, Italo; García-Cunchillos, Iván; Lado, Carlos (Phytotaxa, 2021)
The Myxomycetes comprise a remarkably diverse group of organisms within Amoebozoa, with over 1000 species currently recognized. These organisms, at the end of their life cycles produce fruiting bodies which are the basis for their systematics. Despite being a biodiversity hotspot, the tropical Andes has a myxobiota that remains barely explored so far. In this study, we report the occurrence of three species inhabiting the highlands of the Peruvian Andes between 3000–5000 m.a.s.l. Arcyodes incarnata and Trichia mirabilis are reported for the first time in the Southern Hemisphere and the Neotropics, respectively, while Metatrichia floripara represents the third record in the world, previously only known from Rwanda and Brazil. Fruiting bodies of T. mirabilis were detected as already developed in the field, while the previous reports only included moist chamber culture-derived specimens. These results notably enlarge the geographical distribution of these species and highlight the interest of the tropical Andes, which remains a challenging region to explore and determine its whole myxobiota.